Defect depth estimation in passive thermography - comparing multilayer perceptron with radial basic function networks - Heriansyah, Rudi (2007)
To assist ikohzas and researchers from Malaysia to forge strategic partnership and networking with the JUC members to spur their research & development which will in the end contribute to the wealth of the nation.